Respostas

A melhor resposta!
2014-03-23T12:25:44-03:00
x²+3x-10 ~> a = 1 , b = 3 , c = -10

Δ = b² - 4ac
Δ = 3² - 4.1.(-10)
Δ = 9 - (-40)
Δ = 49

x = -b 
± √Δ
         2a

x = -3 ± 7
         2

x' = -3 + 7 = 4 = 2                x" = -3 - 7 = -10 = -5
          2       2                                2        2


x²-4x-32 ~> a = 1 , b = -4 , c = -32

Δ = b² - 4ac
Δ = (-4)² - 4.1.(-32)
Δ = 16 - (-128)
Δ = 144

x = -b 
± √Δ
         2a

x =
± 12
         2

x' = 4 + 12 = 16 = 8          x" = 4 - 12 = -8 = -4
         2          2                          2         2
3 5 3